THE IMAGE OF ISKANDAR ZULQARNAYN AND THE FIGURE OF ALEXANDER OF MACEDON: A PHILOLOGICAL AND SOURCE-CRITICAL ANALYSIS (International journal of artificial intelligence, 2026)
This article examines the relationship between the Eastern literary-traditional image of Iskandar Zulqarnayn and the historical figure of Alexander of Macedon in Greco-Roman sources. Using comparative textual analysis, motif typology, and historical contextualization, it identifies semantic transformation mechanisms and divergences in naming and narrative layers. The study clarifies how Alexander traditions were culturally adapted and literarily legitimized across regions.